Reply: Should epidural analgesia be abandoned for open pancreatoduodenectomy? - Klotz, Rosa; Larmann, Jan; Knebel, Phillip (JAMA surgery, 2021)
In Reply We appreciate the interest in our article and thank Guerin and Slim for their thoughtful commentary. We reported what is, to our knowledge, the first randomized clinical trial (RCT) comparing epidural analgesia (EDA) and patient-controlled intravenous analgesia (PCIA) after pancreatic surgery focusing on a surgical primary end point. The choice for the primary end point and accordingly, our sample size calculation, was based on a retrospective study suggesting an advantage of PCIA over EDA with regard to gastrointestinal complications. Other previous studies had mainly focused on effectiveness in analgesia and cardiovascular and pulmonary complications. The meta-analysis and cohort study suggested by Guerin and Slim were not considered for sample size calculation because they had not been published when our trial was designed.